ANALISIS STABILITAS TURAP TIANG PADA PEMBANGUNAN DERMAGA JETTY DI DESA KUBU, KUMAI, PANGKALAN BUN, KALIMANTAN TENGAH - Gading Arbi A; Masril Masril; Ana Susanti Yusman (Progressive : Journal of Advanced Engineering and Technology, 2026)
CV.Delta Barito Global is planning to build a new jetty in Central Kalimantan Province. The construction of this new jetty aims to increase coal delivery options to buyers. The initial planning of this new pier uses a jetty type pier with a sheet pile wall bottom structure. The sheet pile wall functions as a soil retainer, the sheet pile wall design uses 508 mm diameter steel pole pipes with varying lengths ranging from 15 m - 30 m. The distance between steel poles is about 30 cm with a spacing of about 30 cm. The distance between steel poles is about 30 cm with WF 200 profile steel bracing to strengthen the position of the steel pipe. The placement of bracing is at a height of 2 m from the top of the pipe. Knowing the condition of pile stability, Knowing recommendations after knowing the condition of pile stability. The following data and methods used for calculations are presented, including the cantilever method, original soil parameters based on SPT investigations, backfill soil parameters, bare rock parameters, subbase course parameters, geotextile specifications, capping beam specifications, steel pipe specifications, manual calculations.The analysis results show the actual penetration depth value of 10 m, the actual diameter value of 508 mm, and the pile deflection of 3 mm. SF1.5 and adjust to the actual conditions that can be realized in the field. The recommendations are to replace sheet pile to steel sheet pile, reduce vehicle load or perform soil improvement.Keywords: pile deflection, pier, pile stability, cantilever pile